Analysis of the Function of Animal Protein Food Demand in Household in The DI Yogyakarta - Ali, Roihan Muhammad; Toiba, Hery; Nugroho, Tri Wahyu (HABITAT, 2024)
Consumption of animal protein food in the Special Region of Yogyakarta is still low compared to consumption of plant food which dominates, so there is a need for a policy from the government to make it easier for households to increase consumption of animal protein food. Animal protein food consumption is influenced by household income and the price of the animal food commodity itself. The aim of this research was to determine the elasticity of household demand for animal protein food and determine the factors that influenced animal food consumption patterns in the Special Region of Yogyakarta. This research utilized data from the 2020 Indonesian National Socioeconomic Survey (Susenas) which covers a total of 3529 households, which the demand for protein food animal origin was estimated using the Quadratic Almost Ideal Demand System (QUAIDS) model. The results of the analysis showed that all variables were significant at the one percent level, which means that animal protein food commodities were influenced by household income, own prices, and prices of other commodity goods as well as socio-demographics (number of household members, age of household heads, education level of household heads, and region) in the Special Region of Yogyakarta. The animal protein food commodity most sensitive to changes in income in the Special Region of Yogyakarta was fish (1.440) followed by meat (1.289), and fish (1.184) as a luxury item while eggs were a normal item (0.469). The Hicksian (compensated) price elasticity values ​​for other commodities in the Special Region of Yogyakarta showed positive results, indicating that these commodities replace each other or were substitutes. Thus, the government could use a pricing strategy to ensure that protein needs for animal food were met in the Special Region of Yogyakarta.